Choosing trigger of ovulation for optimization of in vitro fertilization programs (literature review) - S M Eapen; N G Mishiyeva; B A Martazanova; T V Dontsova; S V Pavlovich (IP Berlin A.V., 2016)
This review presents recent data on the impact of different triggers on the clinical and embryological indicators of the effectiveness of assisted reproductive technology in patients with normal and excessive ovarian response to superovulation. Triggering with gonadotropin releasing hormone agonist can be a real alternative to human chorionic gonadotropin triggering: gonadotropin-releasing hormone agonists trigger reduces the risk of ovarian hyperstimulation syndrome. When modifying the luteal phase, the pregnancy rate after gonadotropin-releasing hormone agonists triggering is comparable with that of human chorionic gonadotropin triggering human chorionic gonadotropin in in vitro fertilization programs.